2015
DOI: 10.3389/fpls.2015.00779
|View full text |Cite
|
Sign up to set email alerts
|

Influence of stripe rust infection on the photosynthetic characteristics and antioxidant system of susceptible and resistant wheat cultivars at the adult plant stage

Abstract: Wheat stripe rust (Puccinia striiformis f. sp. tritici, Pst), is one of the most serious diseases of wheat (Triticum aestivum L.) worldwide. To gain a better understanding of the protective mechanism against stripe rust at the adult plant stage, the differences in photosystem II and antioxidant enzymatic systems between susceptible and resistant wheat in response to stripe rust disease (P. striiformis) were investigated. We found that chlorophyll fluorescence and the activities of the antioxidant enzymes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
70
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 48 publications
9
70
0
Order By: Relevance
“…; Chen et al. ; Farahani and Taghavi ). Similarly, GPX has also been observed to increase in plants that are infected such as sunflowers infected by downy mildew (Herbette et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Chen et al. ; Farahani and Taghavi ). Similarly, GPX has also been observed to increase in plants that are infected such as sunflowers infected by downy mildew (Herbette et al.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we directly attribute the higher ROSscavenging enzyme activity in infected samples to the higher ROS radical activities in infected samples. Ascorbate peroxidase activity has been shown to increase in plants infected by pathogens such as apricot, wheat and mung bean (Hern andez et al 2001;Chen et al 2015;Farahani and Taghavi 2016a). Similarly, GPX has also been observed to increase in plants that are infected such as sunflowers infected by downy mildew (Herbette et al 2003).…”
Section: Ros-scavenging Assaysmentioning
confidence: 99%
“…The extraction of malondialdehyde (MDA) in wheat leaves was performed using thiobarbituric acid (TBA) solution according to the method of Chen et al (2015). After centrifugation, the absorbance of the supernatant was monitored at 532 nm and corrected for nonspecific turbidity by subtracting the absorbance at 600 nm.…”
Section: Measurements Of Malondialdehyde and Electrolyte Leakagementioning
confidence: 99%
“…], Lattanzio et al (2000) reported that lines resistant to aphids ( Aphis fabae Scopoli) showed a flavonoid content higher than the susceptible ones. Chen et al (2015) recently found that after stripe rust infection, chlorophyll fluorescence, and the activities of antioxidant enzymes were higher in resistant wheat than in susceptible wheat.…”
Section: Resultsmentioning
confidence: 99%